'I want to read it in my hands': The aesthetic attraction of independent women's magazines. (1st November 2019) - Webb, Sarah; Fulton, Janet
There is a growing body of evidence suggesting that independent magazines, also known as 'independents', are thriving in Australia's print media industry. As 'maverick' editors, owners and publishers focus more on the design and aesthetic aspects of their publications in response to changing reader expectations, there appears to be a demand for independents among female readers. In particular, young adult female readers are choosing to engage with independent women's magazines in Australia, placing particular emphasis on the aesthetic reading experience offered by the hard-copy format. To explore this phenomenon, a survey and focus group were conducted among women aged 18‐24 years, using Blumler and Katz's Uses and Gratifications theory as the theoretical framework. The initial survey garnered findings from 300 respondents, while the focus group consisted of six participants. One key aspect of the results is that aesthetics is central to understanding the continued appeal and use of such a medium. Other aspects include quality of content, entertainment, escape, collection and habit, and ease of use. In an age where 'digital' is often regarded as the norm, young adult female readers are seeking inspiration and expression from independent women's magazines.